Generation of Fast Magnetoacoustic Waves in the Corona by Impulsive Bursty Reconnection - Sripan Mondal; Abhishekh Kumar Srivastava; David I. Pontin; Eric R. Priest; R. Y. Kwon; Ding Yuan (The Astrophysical Journal, 2024)
Fast-mode magnetohydrodynamic waves in the solar corona are often known to be produced by solar flares and eruptive prominences. Here, we simulate the effect of the interaction of an external perturbation on a magnetic null in the solar corona, which results in the formation of a current sheet (CS). Once the CS undergoes a sufficient extension in its length and squeezing of its width, it may become unstable to the formation of multiple impulsive plasmoids. Eventually, the plasmoids merge with one another to form larger plasmoids and/or are expelled from the sheet. The formation, motion, and coalescence of plasmoids with each other and with magnetic Y-points at the outer periphery of the extended CS are found to generate wavelike perturbations. An analysis of the resultant quasiperiodic variations of pressure, density, velocity, and magnetic field at certain locations in the model corona indicates that these waves are predominantly fast-mode magnetoacoustic waves. For typical coronal parameters, the resultant propagating waves carry an energy flux of 10 ^5 erg cm ^−2 s ^−1 to a large distance of at least 60 Mm away from the CS. In general, we suggest that both waves and reconnection play a role in heating the solar atmosphere and driving the solar wind and may interact with one another in a manner that we refer to as a “symbiosis of waves and reconnection.”